Competition of some minor groove binders for a single DNA binding site - Lah, Jurij (Acta chimica slovenica, 2006)
We employed circular dichroism (CD) and isothermal titration calorimetry (ITC) to characterize binding of netropsin (NET) and distamycin A (DST) to the hairpin (D) formed from the 5-CGAATTGACGTCTCCGTCAATTCG-3 oligonucleotide. From fitting the appropriate model to the CD titration curves describing NET and DST binding to the D and CD and ITC titration curves describing the displacement of NET bound to D by the added DST and vice versa we were able to determine the corresponding binding and displacement constants at 25 °C. The displacement constant (K12) determined for 2DST + NET-D - DST2-D + NET process is in good agreement with the corresponding value calculated from the individual binding events (NET + D -NET-D, k1 = 1.6 106 M-1 DST + D -DST-D, k1 = 1.0 107 M-1 and DST + DST-D -DST2-D, k2 = 0.9 104 M-1). ITC results reveal that the free energy of displacement .G12° = -29 kJ mol-1 in combination with the enthalpy of displacement .H12° = -74 kJ mol-1 results in the corresponding entropy contribution T.S12° = -45 kJ mol-1. Evidently, the 2DST + NET-D -DST2-D + NET displacement is a strongly enthalpy driven process. What we find important with the displacement studies is the observation that NET entirely displaces DST from one half of its 1:1 complexes with the hairpin in spite of the fact that the 1:1 binding constant of NET is about one order of magnitude lower than the corresponding 1:1 constant of DST. We propose that the driving force of this displacement is strong binding of DST molecules that are displaced as a result of the overall NET-DST-D equilibrium to the available DST-hairpin 1:1 complexes.
Keywords: biokemija; cirkularni dikroizem; distamicin; DNA; fizikalna kemija; interakcije; izotermna titracijska kalorimetrija; karakterizacija; makromolekule; netropsin; termodinamika